Man in Modern Islamic Thought: Towards a Contemporary Philosophical Vision of Dignity and Responsibility - Zaman Hassan Khafif, Asst. Lecturer (lark, 2026)
The question of man is one of the most general issues in modern Islamic thought, as it forms a fundamental entry point for understanding the relationship between religion and reality, and the spirit and the mind Freedom with responsibility. With the multitude of cognitive and value-based challenges imposed by the modern era, it has become necessary to reconsider the concept of humanity in light of intellectual and social transformations, ensuring the utilization of the philosophical and ethical dimension that constitutes the essence of the Islamic vision of h uman existence. From this standpoint, the research sought to construct a contemporary philosophical vision of humanity in modern Islamic thought, working to reread the concepts of dignity and responsibility within a context that combines value stability and cognitive engagement. The research objectives were represented in analyzing the philosophical and spiritual foundations upon which the conception of humanity in modern Islamic thought is based, and working to explore the dialectical relationship between dignity and responsibility as two inseparable pillars in the construction of the contemporary Muslim individual. It also worked to compare the intellectual visions of a number of contemporary Islamic thinkers, such as Muhammad Abduh, Muhammad Iqbal, Malik Bennabi, and Taha Abd al-Rahman, to reveal the development of the conception of humanity between religious reference and philosophical reflection. The research adopted the comparative analytical method, through analyzing the intellectual and philosophical texts of modern Islamic reformist thinkers, and comparing their contents in light of the central concepts of dignity, freedom, and responsibility The study also employed critical synthetic research to reconstruct concepts in accordance with the requirements of contemporary human thought, while utilizing some modern philosophical analytical tools in approaching the Islamic text without compromising its referential specificity. The research reached a number of conclusions, including that modern Islamic thought has presented a qualitative shift in the understanding of humanity. Humans are no longer merely honored beings in the text, but have become moral and historical agents whose dignity is derived from their capacity for awareness, experience, and action. The results also showed that dignity in the Islamic conception is not an absolute praise but a responsibility conditioned by conscious action, and that the relationship between dignity and responsibility is based on the principle of balance between freedom and obligation.